Answer: It's an algebraic expression
Step-by-step explanation: k²- 11 is an algebraic expression.
If you found my answer helpful please choose my answer as Brainliest. I would appreciate it! Good luck everyone! :)
Answer:
<h2>A) y = -5x - 8</h2>
Step-by-step explanation:
The point-slope form of an equation of a line:
![y-y_1=m(x-x_1)](https://tex.z-dn.net/?f=y-y_1%3Dm%28x-x_1%29)
m - slope
(x₁, y₁) - point on a line
We have the slope m = -5, and the point (-1, -3). Substitute:
![y-(-3)=-5(x-(-1))\\\\y+3=-5(x+1)](https://tex.z-dn.net/?f=y-%28-3%29%3D-5%28x-%28-1%29%29%5C%5C%5C%5Cy%2B3%3D-5%28x%2B1%29)
Convert to the slope-intercept form (y = mx + b):
<em>use the distributive property</em>
<em>subtract 3 from both sides</em>
![y=-5x-8](https://tex.z-dn.net/?f=y%3D-5x-8)
Answer:
8^2 = b^2 + 4^2
Step-by-step explanation:
1 hour = 3600 seconds
3 × 3600 = 10800
<span>10800 yards per hour
</span>
1 mile = 1760 yards
10800 ÷ 1760 = 6.13
6.13 miles per hour
We have
.
First let us factor the 2 to obtain,
![2(x^2-4)](https://tex.z-dn.net/?f=2%28x%5E2-4%29)
We can now see clearly that the expression inside the parentheses is a difference of two squares.
We now write the 4 as 2². So that we obtain the expression,
![2(x^2-2^2)](https://tex.z-dn.net/?f=2%28x%5E2-2%5E2%29)
Recall that
![a^2-b^2=(a+b)(a-b)](https://tex.z-dn.net/?f=a%5E2-b%5E2%3D%28a%2Bb%29%28a-b%29)
Hence our expression becomes,
![2(x+2)(x-2)](https://tex.z-dn.net/?f=2%28x%2B2%29%28x-2%29)
Therefore, when factored completely,
![2x^2-8=2(x+2)(x-2)](https://tex.z-dn.net/?f=2x%5E2-8%3D2%28x%2B2%29%28x-2%29)